Impact of vitamin D supplementation in the prognosis of patients with SARS-CoV2 pneumonia admitted to the intensive care unit – a randomized controlled trial - Gonçalves, Ana Moura; Rodrigues, Bárbara Sucena; Antunes, Maria Lobo; Gonçalves, João; Marinho, António (Frontiers in Immunology, 2025)
BackgroundResearch suggests that patients with low vitD levels are more susceptible to severe SARS-CoV-2 infections with need for hospitalization and admission to an intensive care unit (ICU). Our objectives were to evaluate the impact of cholecalciferol supplementation in critical care patients with severe SARS-CoV-2 pneumonia in regards to prognosis, evolution of organ failure and need for organ support.MethodsA nonblinded controlled trial was conducted in patients with severe SARS-CoV-2 pneumonia admitted to the ICU. Patients were randomized by block of two, into three groups (no cholecalciferol, 500MU cholecalciferol arm, 2MU/day cholecalciferol during ICU stay and remaining hospitalization). Serum 25-hydroxyvitamin D levels were measured and correlated with organ failure indicators (based on SOFA), ICU length of stay, need for organ support, days on mechanical ventilation and ICU, intra-hospital and 60 day mortality.Results207 patients were included. The number of organ failures showed a significant negative correlation with 25vitD levels on admission (r= -0.208, p=0.005), on the third day (r= -0.312, p<0,001), and on the seventh day(r= -0.224, p=0.01). In the group of patients supplemented with 500MU of cholecalciferol there was a significant negative correlation between the number of organ failures and 25vitD levels on third day (r= -0.454, p<0.001).ConclusionsLower vitD levels on admission were related to more organ failures and high doses cholecalciferol supplementation was related to lower organ failures. More studies are needed to evaluate the impact of baseline vitD levels on clinical outcome and prognosis, to identify potential subpopulations that can benefit from supplementation and to understand the impact of critical illness on cholecalciferol action and protective effect.